The Moral Value of Abstinence for the People of Bukit Kemuning Village, Kampar Regency - Asina Lamtiar Simanjuntak; Muhammad Mukhlis (UIR Press, 2022)
Abstinence is a prohibition or provision that as far as possible cannot be violated by the community because it contains values ​​that can control how every community behaves in everyday life. The belief of the Bukit Kemuning village community towards taboos in modern times makes the writer interested in further researching what taboos are and the moral values ​​contained in them. For this reason, the problems in this study are 1) How are moral values ​​related to moral responsibility in abstinence in the village of Bukit Kemuning, Kampar Regency? 2) How are moral values ​​related to human conscience in abstinence from the people of Bukit Kemuning Village, Kampar Regency? 3) How are moral values ​​related to human rights and obligations in the prohibition against prohibition in the village of Bukit Kemuning, Kampar Regency? The theory used in this research is Hamidy (1995) and Salam (2012). The method used in this research is descriptive method. The approach used in this study is a qualitative approach. The technique used in this research is the interview technique. The results of this study found as many as 55 data. Moral values ​​related to human moral responsibility totaled 26 data, moral values ​​related to human conscience amounted to 17 data, and moral values ​​related to human rights and obligations amounted to 12 data. So it can be concluded that the village community of Buki Kemuning prioritizes abstinence related to moral values ​​to behave better in everyday life.